Proposta de normatização para a gestão dos resíduos sólidos na Universidade Federal de Lavras - Paula, Cristiane Angélica de Paiva (2015)
Universities present residue-generating capability comparable to small urban centers. The residues produced at the universities are qualitatively distinct due to the development of education, research and extension activities, in addition to administrative activities, with the possibility of presenting hazardous traits to human health and the environment. The Universidade Federal de Lavras (UFLA) generates many residues, with significant generation of chemical, biological, recyclable, organic, of civil construction, lamps, agrochemical, electro-electronics, among others. The present study, based on bibliographic and legislative research as well as on non-structured interviews, sought to propose a Resolution Project for the adequate managing of chemical, biological, recyclable and of civil construction residues at UFLA. Despite the existence of the management of residues generated at the campus, we observed the lack of integration by part of the departments and sectors at UFLA in this aspect, leading to the inefficiency of many stages of management. The universities present administrative autonomy, thus, they are capable of formulating their own norms, which must be approved by the University Councils. Therefore, the formulation and approval of internal environmental norms at UFLA are indispensable for environmental knowledge and environmentally adequate attitudes are no longer isolated practices at the campus to become concrete for the entire academic community, guaranteeing the formation of environmentally conscious future professionals.